The Fruit of Teaching Epidemiology and Biostatistics to Undergraduate Medical Students. - Raheem, Yousif A. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: All medical colleges give students courses in epidemiology and biostatistics to help them in understanding medical data and to prepare them to conduct graduate and professional research. After graduation, understanding and correct application of the principles of epidemiology and biostatistics help the physicians in making better diagnostic and management decision based on best evidence.Patients and Methods: A cross-sectional questionnaire-based survey was carried out among junior (chronic resident) doctors at several hospitals in Baghdad from the 1st of January till the 31st October 2009. A total of 212 physicians answered the questionnaire which covered demographic characteristics, average score of graduation, number of published or accepted to publish researches, reading health/medical journals, understanding the methods and statistical analysis of research and the answers of 25 multiple choice questions (MCQs) in basic epidemiology and biostatistics.Results: No physician conducted or participated in any medical or health research. Only 19.34% of them read medical/health journals regularly, 29.72% read occasionally, and 50.94% not read. For those who read the medical/health journals regularly or occasionally (104 respondents), 42.31% not understand the methods and the statistical analysis of the researches. For those who not read (108 respondents), 61.11% blame the difficulty of the methods and statistics of researches as a main cause to flee from the journals. The mean of the MCQs exam was 62.38% (which is not very promising), more than 50% 0f the physician got score below 55%, and more over, about one third failed in the exam.Conclusion: Improving our students (who will become doctors) experience of learning and knowledge of epidemiology and biostatistics courses is an urgent need to meet the evidence based transition in medicine.